Pengaruh Ulasan dan Rating Produk terhadap Minat Beli Berdasarkan Kelompok Usia pada Platform E-commerce - Andri Suwendi; Nabila Indriani; Najla Sahla Sahira; Mia Lasmi Wardiyah (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
This study aims to determine whether there is a significant difference in the influence of product reviews and ratings on purchase intention on e-commerce platforms based on age groups. The research used a quantitative approach with a comparative design. A total of 42 respondents participated, consisting of 21 individuals under the age of 25 and 21 individuals over the age of 25. Data were collected using a Likert-scale questionnaire covering three main aspects: product reviews, product ratings, and purchase intention. All 15 statements in the questionnaire were tested and found to be valid. Data analysis included validity testing, reliability testing, normality testing, and the Mann-Whitney U test to compare age groups. The results showed a significant difference between the two age groups regarding the influence of reviews and ratings on purchase intention. These findings indicate that age influences how individuals respond to evaluative information on e-commerce platforms. Therefore, digital marketing strategies should consider demographic differences to more effectively target diverse consumer groups.